Tașmīm al-Waḥdah al-Ta'līmiyyah fi al-Mubtada' wa al-Khabar al-Muassasah 'alā Amṡilah al-Ayat al-Qur'aniyyah - Yasin, Agus; Sofyan, Rifqi Nauval (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
The purposes of this study are (1) to explain the characteristics of the teaching module of the Mubtada' and Khabar with examples of the al-Qur'an and (2) to know the effectiveness of the teaching module of Mubtada' and Khabar with examples of the al-Qur'an for middle-level Arabic students. This research is a type of Research & Development with the Borg & Gall model. The researcher uses interviews, lifts, tests, and documents in data collection. The researchers used the Mann-Whitney Test formula for quantitative data analysis. This study introduced a module designed, contained from beginning to end, that is an independent learning that can be used, read, and understood by students without a teacher's explication directly. Another important finding was that the researcher found that this module is effective in improving the student's understanding of the Mubtada' and Khabar.